PENGARUH CITRA MEREK TERHADAP MINAT MASYARAKAT UNTUK MEMBELI PRODUK TABUNGAN SYARIAH DI BTM DINAR NASYIAH 01 BOJONEGORO - Emiarti, Endah (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
This research aims to determine the partial and determinative influence of brand image on community interest in saving with Sharia savings products at KSPPS BTM Dinar Nasyiah 01 Bojonegoro. The population of this study were all participant of BTM Dinar Nasyiah 01. The sample in this study was 100 respondents, determined using purposive sampling technique. The data used were primary data obtained from respondents' answers through distributed questionnaires. Data processing was carried out using SPSS (Statistical Package for Social Science) with simple linear analysis method. The results of this study indicate that brand image has a positive and significant influence on community interest. The management should focus more on branding the image of the syariah saving product so that can increase the sales.